2012
DOI: 10.1007/s13191-012-0198-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Shear Bond Strength of Zirconia Bonded to Dentin After Various Surface Treatments of Zirconia

Abstract: This study evaluated the shear bond strength of zirconia bonded to dentin specimens using a self etch dual cure resin cement after various surface treatments of zirconia. Twenty zirconia rods (3 × 2.5 mm) were prepared from zirconia blocks and assigned into 5 groups for the following surface treatments. (1) Group I: Control (C) no treatment (2) Group II: airborne-particle abrasion (APA), (3) Group III: hydrofluoric acid etching (HF), (4) Group IV: hydrofluoric acid etching followed by silanation (HF/S), and (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 19 publications
2
20
0
1
Order By: Relevance
“…15 Reddy et al showed that the application of a primer provides a stronger bond between zirconia and resin cement than sandblasting. 16 Thus, in this study, we did not perform sandblasting and only assessed the effect of the type of adhesive on the microshear bond strength of resin cement to zirconia.…”
Section: Discussionmentioning
confidence: 99%
“…15 Reddy et al showed that the application of a primer provides a stronger bond between zirconia and resin cement than sandblasting. 16 Thus, in this study, we did not perform sandblasting and only assessed the effect of the type of adhesive on the microshear bond strength of resin cement to zirconia.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the sandblasting pressure was decreased in to 2 bar, and to 1 bar, since many authors recommended the use of low air pressure in sandblasting of the zirconia to avoid micro flaws and cracks creation which decreases the mechanical properties of zirconia and also may cause phase transformation of zirconia from the tetragonal to the monoclinic phase (24).…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] Resin cement–zirconia bond can be improved through various methods such as the micromechanical means of airborne-particle abrasion[ 10 11 12 ] or chemical activation with specific monomers such as 10-methacryloyloxydecyl dihydrogen phosphate (MDP) and 4-methacryloxy ethyl trimellitic anhydride. [ 13 14 15 16 17 ]…”
Section: Introductionmentioning
confidence: 99%